Clinical–radiological correlations in COVID‐19‐related venous thromboembolism: Preliminary results from a multidisciplinary study. Issue 9 (29th May 2021) - Wu, Maddalena Alessandra; Colombo, Riccardo; Arquati, Massimo; Ippolito, Sonia; Taino, Alba; Ruggiero, Diego; Tonelli, Francesca; Trombetta, Lucia; Facchinetti, Pietro; Glielmo, Pierluigi; Cogliati, Chiara; Flor, Nicola
Abstract: Introduction: Among the multiple complex pathophysiological mechanisms underlying COVID‐19 pneumonia, immunothrombosis has been shown to play a key role. One of the most dangerous consequences of the prothrombotic imbalance is the increased incidence of micro‐ and macrothrombotic phenomena, especially deep vein thrombosis (DVT) and pulmonary embolism (PE). Methods: We investigated the correlation between radiological and clinical–biochemical characteristics in a cohort of hospitalised COVID‐19 patients. Results: PE was confirmed in 14/61 (23%) patients, five (35.7%) had DVT. The radiographic findings, quantified by Qanadli score calculated on CT angiography, correlated with the clinical score and biochemical markers. The ratio between the right and left ventricle diameter measured at CT angiography correlated with the length of hospital stay. Conclusion: In our cohort radiological parameters showed a significant correlation with clinical prognostic indices and scores, thus suggesting that a multidisciplinary approach is advisable in the evaluation of PE in COVID‐19 patients.